EVALUATION OF EDTA DEPENDENT PLATELET CLUMPING RESULTING IN PSEUDO THROMBOCYTOPENIA (The Research of Medical Science Review, 2025)
Background: Pseudo thrombocytopenia is defined as a low platelet count, caused by EDTA dependent platelet aggregation. Pseudo thrombocytopenia has no clinical significance. It misdiagnosis may lead to unnecessary diagnostic tests and treatment. Objective: To evaluate the frequency of EDTA dependent pseudo thrombocytopenia in a laboratory setting. Methodology: It is a cross sectional study and enrolled 500 participant’s samples. The both male and female came for complete blood count (CBC) was initially enrolled. Later on only participants had low platelet count in EDTA vaccutainers were enrolled for further analysis. After taking verbal informed consent, about three to five milliliter blood was taken in EDTA and sodium citrate vaccutainers separately. The platelet count was estimated through automated hematology analyzer. The data was analyzed through (SPSS v.25.0). Results: From total of 240 participants, more male participants (60.41%) were observed as females (39.58%). The mean (+ standard deviation) age was 26.66+5.031. It has been observed that the 31.25% participants had low platelet count when measuring in EDTA vaccutainer. While in sodium citrate vaccutainer only 10.0% had low platelet count. It has been found that sodium citrate vaccutainer is more reliable for platelet count estimation (p=0.001). Conclusion: EDTA dependent PTCP is a laboratory artifact that has serious effects for patients. In the present study, sodium citrate anticoagulant effectively corrected EDTA dependent PTCP in 21.25% of the patients.